Safety and efficacy of rituximab in patients with diffuse large B-cell lymphoma in Malawi: a prospective, single-arm, non-randomised phase 1/2 clinical trial. Issue 7 (July 2021) - Kimani, Stephen; Painschab, Matthew S; Kaimila, Bongani; Kasonkanji, Edwards; Zuze, Takondwa; Tomoka, Tamiwe; Mulenga, Maurice; Nyasosela, Richard; Chikasema, Maria; Mtangwanika, Asekanadziwa; Chawinga, Mena; Mhango, Wilberforce; et al.
Summary: Background: There are no clinical trials involving patients with diffuse large B-cell lymphoma (DLBCL) in sub-Saharan Africa since antiretroviral therapy (ART) for HIV became widely available in this region. We aimed to establish the safety and efficacy of rituximab plus cyclophosphamide, doxorubicin, vincristine, and prednisone (R-CHOP) in patients with DLBCL in Malawi. Methods: This prospective, single-arm, non-randomised phase 1/2 clinical trial was done at Kamuzu Central Hospital Cancer Clinic (Lilongwe, Malawi). Eligible patients were adults (aged 18–60 years) with newly diagnosed DLBCL, an Eastern Cooperative Oncology Group performance status of 0–2, a CD4 count of 100 cells per μL or higher (if HIV-positive), measurable disease by physical examination, an absolute neutrophil count of 1000 × 10 9 cells per L or higher, a platelet count of 100 × 10 9 platelets per L or higher, a serum creatinine concentration of 132·60 μmol/L or less, a total bilirubin concentration of 34·21 μmol/L or less, a negative urine pregnancy test in women of childbearing potential, and no previous cytotoxic therapy. Pregnant or breastfeeding women, and individuals with CNS involvement from DLBCL, chronic hepatitis B infection (unless they were receiving tenofovir plus lamivudine), or any other comorbidities that would compromise the protocol objectives were excluded. Eligible patients received intravenous rituximab 375 mg/m 2, cyclophosphamide 750 mg/m 2, doxorubicin 50 mg/m 2, and vincristine 1·4 mg/m 2 (maximum 2 mg/m 2 ), and oral prednisone 100 mg or an equivalent drug every 21 days for up to six cycles. HIV-positive patients received concurrent ART. The primary outcome was the proportion of patients with National Cancer Institute Common Terminology Criteria for Adverse Events grade 3 or 4 non-haematological toxic effects or treatment-related deaths after six cycles of treatment. Secondary efficacy outcomes included the proportion of patients with a complete response after six cycles of treatment, and progression-free survival and overall survival at 12 months and 24 months. This trial is registered with ClinicalTrials.gov, NCT02660710 . Findings: Between Aug 1, 2016, and July 31, 2019, 76 patients were screened, of whom 37 were eligible for the study and received R-CHOP. The median age of patients was 44 years (IQR 39–49) and 16 (43%) were women. Of all 37 patients, 20 (54%) had stage III or IV DLBCL, and the age-adjusted international prognostic index was 2 or higher in 25 (68%) patients. 27 (73%) patients were HIV-positive, with a median CD4 count of 208 cells per μL (IQR 144–422), and 21 (78%) patients were receiving ART at enrolment. Patients completed a median of six cycles (IQR 4–6). Grade 3 or 4 non-haematological toxic effects were reported in 12 (32% [95% CI 19–49]) patients, the most common of which was infection (nine [24%] patients). Of 16 (43%) deaths, ten were due to progression of DLBCL, four were due to treatment-related complications, and two were due to other causes, yielding a treatment-related mortality of 11% (95% CI 4–26%). Grade 3 or 4 neutropenia was observed in 26 (70%) patients, and grade 3 or 4 anaemia was observed in 11 (29%) patients. A total of 22 (59%) patients had a complete response. Overall survival was 68% (95% CI 50–80) at 12 months and 55% (37–70) at 24 months, and progression-free survival was 59% (42–73) at 12 months and 53% (35–68) at 24 months. Interpretation: R-CHOP could be feasible, safe, and efficacious in patients with DLBCL in Malawi. This is the first completed clinical trial on DLBCL focused on sub-Saharan African populations. Given the paucity of data on treatment of DLBCL from this region, these results could inform emerging cancer treatment programmes in sub-Saharan Africa. Funding: The University of North Carolina Lineberger Comprehensive Cancer Center.